Traditional complementary feeding or BLW (Baby Led Weaning) method? – A cross-sectional study of Polish infants during complementary feeding - Białek-Dratwa, Agnieszka; Kowalski, Oskar; Szczepańska, Elżbieta (Frontiers in Pediatrics, 2022)
Baby-led weaning (BLW) is an increasingly well-known method of complementary feeding for infants. The BLW method is based on the fact that the baby becomes physically ready to eat on its own and can henceforth effectively supplement its diet, which was previously based on breast milk or formula milk. Material and method: a cross-sectional survey was conducted in April 2022 among mothers of children from 6 months to 36 months of age residing throughout Poland. After considering inclusion and exclusion criteria, information collected from 646 women was included in the final analysis. Results: The study group was divided into three subgroups: mothers using BLW (M-BLW), mothers not familiar with the BLW method (M-NoBLW)), mothers not using the BLW method - mothers using the spoon-feeding method) (M-TS). Among the mothers surveyed, 413 women (63.93%) used the BLW method, 222 mothers (34.36%) did not use the BLW method of which 50 (7.73%) of these were unfamiliar with the method, and 172 (26.62%) simply did not use it. Among M-TS mothers, the child was most often entirely or mostly spoon-fed by an adult (73.84%), and the same was true for the M-NoBLW group (70.0%). In the M-BLW group, 58.60% of children were half-fed by an adult with a spoon. half ate independently. Conclusions: Infants fed by the BLW method were more likely to have their diets expanded after 6 months of age, they were also more likely to be given products from the family table than children fed traditionally with a spoon. Full BLW was implemented by only 29% of children in the BLW group. The vomiting reflex, spitting food out of the mouth, and gagging, were more common among children fed by the BLW method. In contrast, choking occurred comparably often in both groups - in 5.4% of spoon-fed children and 6.9% of BLW-fed children.